EuroLaunch - A DLR and SSC Cooperation for Sounding Rocket and Balloon Missions - Schmidt, Alexander; Turner, Peter; Kemi, Stig; Poromaa, Lernnart (SpaceOps 2012 Conference, 2012)
EuroLaunch is a cooperation between the German Aerospace Center (DLR) and SSC in the field of sounding rocket and balloon activities. DLR and SSC are well equipped for supporting most types of sounding rocket and balloon missions using Esrange Space Center, the SSC launch facility, as the prime range or any other worldwide location depending on the scientific mission requirements. Esrange Space center is located north the Arctic Circle near the city of Kiruna. Esrange as well as the Mobile Rocket Base (DLR-MORABA) provides all expertise and infrastructure for the launch of sounding rockets and stratospheric balloons. The collaborative coordination of services and infrastructures creates an efficient, cost effective and flexible partner for sounding rocket- and balloon missions. Both partners have long experience in the sounding rocket and balloon business and EuroLaunch will continue to create synergies to the benefits of the customers. The paper gives an overview over completed, ongoing and future activites of EuroLaunch as well as over all the resources provided, for example facilities at Esrange, mobile infrastructure of MORABA, vehicle systems, payload systems and logistics.